Plant science in action - Caroline Barnes (Hodder and Stoughton, 1994)
The book explores how an understanding of plant physiology and behaviour has influenced the cultivation of crop species in agriculture and horticulture over the years, and all over the world. As the book investigates the science underlying animal farming techniques, it takes care to consider their social, aconomic and political implications, and look into the complex environmental and ethical issues surrounding food production for ever increasing world population